1991
DOI: 10.1038/ki.1991.31
|View full text |Cite
|
Sign up to set email alerts
|

Direct vasopressor effect of recombinant human erythropoietin on renal resistance vessels

Abstract: The contractile properties of recombinant human erythropoietin (rHuEPO) on isolated resistance vessels of renal and mesenteric vascular beds were studied in an in vitro model using a small vessel myograph. Under isometric conditions, rHuEPO caused a contraction of this vasculature in a concentration range between 10 U/ml and 200 U/ml. A maximal active wall tension of 1.52 +/- 0.19 mN/mm was obtained under a rHuEPO dose of 200 U/ml. In Ca2+ free solution, the pressor response to high rHuEPO-concentrations was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(97 citation statements)
references
References 18 publications
2
93
1
1
Order By: Relevance
“…Recombinant human EPO (rHuEPO) causes contraction of isolated resistance vessels of the renal and mesenteric vascular beds. 7 These effects are endothelium independent and are not abolished by calcium antagonists or angiotensin II (AII) receptor antagonists. In cultured human coronary artery cells EPO causes dosedependent inhibition of basal and acetylcholine stimulated nitric oxide (NO) production and eNOS protein expression suggesting that EPO may also alter vascular reactivity by endothelium dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant human EPO (rHuEPO) causes contraction of isolated resistance vessels of the renal and mesenteric vascular beds. 7 These effects are endothelium independent and are not abolished by calcium antagonists or angiotensin II (AII) receptor antagonists. In cultured human coronary artery cells EPO causes dosedependent inhibition of basal and acetylcholine stimulated nitric oxide (NO) production and eNOS protein expression suggesting that EPO may also alter vascular reactivity by endothelium dependent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Cortisol treatment also causes suppression of the nitric oxide system as evidenced by reduced plasma nitrate/nitrite concentrations. 5 In the context of these observations, Correspondence 6,7 EPO-induced hypertension has also been demonstrated to be due in part to nitric oxide resistance. 8 The aim of the current study was to examine the role of EPO as a possible mediator of cortisolinduced hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which rHuEPO induces hypertension has been in the past explained by an increase of blood viscosity strongly related to the hematocrit (Mayer et al 1988 ;Raine 1988), or vasoconstriction elicited by improvement of hypoxia (Eschbach et al 1987 ;Kamata et al 1991). Recently, Heidenreich et al (1991) have reported that rHuEPO has a direct vasopressor effect on renal and mesenteric resistance vessels of normotensive Wistar-Kyoto rats in vitro and that threshold concentration for a pressor response to rHuEPO is 10 U/ml. They suggest that the vasopressor capacity of rHuEPO may contribute to the development of hypertension seen in rHuEPO-treated dialysis patients and may amplify or aggravate other relevant pathomechanisms of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Heidenreich et al (1991) have reported that rHuEPO has a direct vasopressor effect on proximal resistance vessels taken from Wistar-Kyoto rats without renal failure, which may contribute to the development of hypertension seen in rHuEPO-treated dialysis patients. Therefore, the present study was designed to determine whether rHuEPO has direct effects on mean arterial pressure (MAP) or renal hemodynamics in anesthetized rabbits without renal failure.…”
mentioning
confidence: 99%
“…However, complications such as newly originated hypertension, worsening of previous hypertension, thrombosis of arteriovenous fi stula, and hyperkalemia can be caused by the use of rhEPO. [1][2][3][4] Hypertension induced with the use of erythropoietin in therapy is a complication which affects prognosis in patients treated with dialysis. 5,6 The exact mechanism of hypertension caused by rhEPO is not yet known.…”
mentioning
confidence: 99%